Easy computer basics : see it done. do it yourself. - Miller, Michael (Indianapolis, Indiana : Que Corporation, 2008)
Provides information on the basics of Windows Vista and personal computers, covering such topics as hardware, applications, files and folders, searching the Internet, playing music and movies, working with pictures, home networks, and security.